2003
DOI: 10.1177/154405910308200707
|View full text |Cite
|
Sign up to set email alerts
|

Segregation Analysis of Mandibular Prognathism in Libya

Abstract: The etiology of mandibular prognathism has been attributed to various genetic inheritance patterns and some environmental factors. The variation in inheritance patterns can be partly due to the use of different statistical approaches in the respective studies. The objective of this study was to investigate the role of genetic influences in the etiology of this trait. We performed segregation analysis on 37 families of patients currently being treated for mandibular prognathism. Mandibular prognathism was treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
2
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 19 publications
6
56
2
3
Order By: Relevance
“…A maior parte das anomalias craniofaciais não tem características monogênicas 5,6,7,10,11,17,25 , ou seja, definidas por apenas um gene. Normalmente apresentam penetrância incompleta, que é a ausência de expressão fenotípica em uma porcentagem de indivíduos que apresentam um dado genótipo.…”
Section: A Genética E Os Problemas Craniofaciaisunclassified
See 2 more Smart Citations
“…A maior parte das anomalias craniofaciais não tem características monogênicas 5,6,7,10,11,17,25 , ou seja, definidas por apenas um gene. Normalmente apresentam penetrância incompleta, que é a ausência de expressão fenotípica em uma porcentagem de indivíduos que apresentam um dado genótipo.…”
Section: A Genética E Os Problemas Craniofaciaisunclassified
“…De acordo com a literatura, os fatores genéticos são claramente predominantes durante a morfogênese craniofacial embriológica, enquanto o ambiente é o principal fator quando se considera a morfologia dentofacial pós-natal, particularmente durante o crescimento da face 4,6,17 . Dessa forma, alguns autores advogam que o complexo craniofacial apresenta um potencial intrínseco de crescimento, mas é suscetível a condições biomecânicas ambientais 5,12,13,25 . É altamente provável que em pacientes que apresentem distúrbios no processo normal de crescimento e desenvolvimento craniofacial, estas condições possam ser precipitadas pela herança de genes que predisponham àquela morfologia craniofacial alterada 5 .…”
Section: A Genética E Os Problemas Craniofaciaisunclassified
See 1 more Smart Citation
“…The etiology of class III malocclusion is a curious issue and there is much to be clarified and understood. To describe class III malocclusion, environmental and genetic factors are playing the major role and it follows the autosomal dominant mode of inheritance was confirmed from altered studies 1,7,8) . However, the relationship concerning cranialbase morphology related to genetic heritability and Class III malocclusion is not entirely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic analysis of families with the Class III phenotype supports the hypothesis of polygenic inheritance. [4][5][6][7] Recently, Cruz et al 8 in a study on 55 Brazilian families with mandibular prognathism concluded that there is a major gene that influences the expression of the trait with clear signs of Mendelian inheritance.…”
Section: Introductionmentioning
confidence: 99%